2015
DOI: 10.1155/2015/403950
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant and Anticholinesterase Potential of SixThymusSpecies

Abstract: The present study aimed to evaluate antioxidant and acetylcholinesterase (AChE) inhibitory activities of the ethanolic extracts of six selected Thymus species growing in Croatia (T. longicaulis, T. praecox subsp. polytrichus, T. pulegioides, T. serpyllum subsp. serpyllum, T. striatus, and T. vulgaris). Antioxidant effectiveness was assessed using six different assays, in comparison with rosmarinic acid, luteolin, and reference antioxidants. All tested Thymus extracts possessed DPPH (IC50 = 3–6 μg/mL) and nitri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
58
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 57 publications
(62 citation statements)
references
References 39 publications
3
58
0
1
Order By: Relevance
“…polytrichus, T. pulegioides, T. serpyllum subsp. serpyllum, T. striatus, and T. vulgaris were demonstrated inhibitory activity against AChE [18]. This activity may be caused from carvacrol, which is one of most important compounds of Thymus species [40].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…polytrichus, T. pulegioides, T. serpyllum subsp. serpyllum, T. striatus, and T. vulgaris were demonstrated inhibitory activity against AChE [18]. This activity may be caused from carvacrol, which is one of most important compounds of Thymus species [40].…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, many researchers have conducted studies on the antidiabetic activities of Salvia and Lamium species to date [15,16]. Also, literature survey clearly demonstrated that there are many studies on anticholinesterase activity of different Origanum, Salvia, and Thymus species [17][18][19].…”
mentioning
confidence: 99%
“…The oils of T. schimperi possess antifungal and antibacterial activity against different species of fungus and bacteria [3,11,40,43] which was similar with pharmacologic activity of oils of T. hirtus, T. kotschyanus boiss, T. vulgaris, T. mastichina, T. serpyllum and T. algeriensis species [28,41,46,47]. T. schimperi oil had antioxidant and preservative effects [4] and consistent with other species of thymus [2,41,44,46,48,49] and seem to be applicable in both medicine and food industry. The oils of T. serrulatus and T. schimperi from different Ethiopian localities had promising protective activity against paracetamol induced hepatic damage in rats [30].…”
Section: Pharmacological Properties Of T Schimperi and T Serrulatusmentioning
confidence: 70%
“…serpyllum had potent effect on inhibition of human tumor cells lines growth [44]. T. longicaulis, T. pulegioides, T. vulgaris, T. serpyllum, T. striatus and T. praecox also showed anti-acetylcholinesterase activities [2]. All this entire species of thymus had comparable pharmacologic property with T. schimperi and T. serrulatus.…”
Section: Pharmacological Properties Of T Schimperi and T Serrulatusmentioning
confidence: 99%
See 1 more Smart Citation